2018
DOI: 10.1111/ijd.14050
|View full text |Cite
|
Sign up to set email alerts
|

Hydroa vacciniforme‐like lymphoproliferative disorder in an elderly Chinese patient and a literature review of adult cases

Abstract: Hydroa vaccinforme-like lymphoproliferative disorder (HVLPD) is a rare T-cell lymphoproliferative disorder driven by the Epstein-Barr Virus (EBV). It was initially designated under the 2008 WHO classification of tumors of hematopoietic and lymphoid tissues as a distinct entity but has been recently reclassified as a lymphoproliferative disorder under the 2016 revision of the 2008 WHO classification of lymphoid malignancies. HVLPD mainly affects Asian, Central, and South American children. It is rarely seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These cases with extracutaneous involvement of atypical lesional cells are diagnosed as systemic EBV+ T-cell lymphoma of childhood according to the revised 4th WHO classification 1 , 2 . Although classic HVLPD usually occurs in the pediatric age group, there have been cases of systemic EBV+ T-cell lymphoma in adults with HVLPD 3 , 5 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These cases with extracutaneous involvement of atypical lesional cells are diagnosed as systemic EBV+ T-cell lymphoma of childhood according to the revised 4th WHO classification 1 , 2 . Although classic HVLPD usually occurs in the pediatric age group, there have been cases of systemic EBV+ T-cell lymphoma in adults with HVLPD 3 , 5 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…69,75,93 Furthermore, several studies have found that patients who get chemotherapies have a worse prognosis than those who do not. 73,92 Most of the data available in this field considered the CHOP regimen as the main therapy, and as we explained earlier, CHOP is an anthracycline-based regimen that is not effective in F I G U R E 2 Treatments for EBV associated LPDs. Four types of treatments are suggested to be effective against EBV associated LPDs: chemotherapy, immunotherapy, targeted therapy and hematopoietic stem cell transplantations.…”
Section: Sys Caebv Hv and Smbamentioning
confidence: 99%
“…These three subtypes of EBV NK/T LPDs, which have close relevance, have not responded well to chemotherapies. 13,71,73,32,92 Unfortunately, due to the rarity of these disorders, finding an effective therapy has been difficult. No effective treatments, except HSCT, have been suggested for patients with sys CAEBV, HV, and SMBA.…”
Section: Sys Caebv Hv and Smbamentioning
confidence: 99%
See 2 more Smart Citations